Orthognathic surgery in patients with large condylar destructions - Sant'Ana, Eduardo; Dias-Ribeiro, Eduardo [UNESP]; De Lima, Valthierre Nunes [UNESP]; Correa, Ana Paula Simoes [UNESP]; Sonoda, Celso Koogi [UNESP]; Nogueira, Renato Luiz Maia (Wolters Kluwer, 2016)
Condylar resorption is understood as changes in shape and volume of the condylar bone, due to local, systemic, and iatrogenic factors. The occurrence of condylar resorption after orthognathic surgery can occur when the condylar repositioning in mandibular fossa is performed improperly. In addition, systemic diseases such as osteoarthritis and rheumatoid arthritis seem to influence this process. The aim of this study was to report 3 cases of patients with severe condylar alterations, submitted to orthognathic surgery for treatment of dentofacial deformities. Considerations regarding the diagnosis, surgical planning (counterclockwise rotation), surgical techniques (bilateral sagittal split osteotomy, bimaxillary osteotomies, rigid fixation, maxillomandibular fixation period), and results (short terms) are discussed.
Keywords: Mandibular condyle; Orthognathic surgery; Resorption; Treatment planning